Computer Science in Information Retrieval System: Tools and Techniques - Chandran, Ranjita; Ramananda, B. S. (Journal of Information and Knowledge, 1985)
The role of information worker in the computer environment is discussed. Various steps involved in the computer based Selective Dissemination of Information (SDI) and generating Comparative Product Profile (COPP) are analysed. Some of the computer techniques and tools are examined and their application in design and development of SDI and COPP systems are highlighted. Concludes that the knowledge and skills of handling computers for information dissemination and retrieval should form an essential component of Information science.